ANALISIS DINAMIKA POLITIK ISLAM DI ASIA TENGGARA: Studi Historis Komparatif Indonesia dan Malaysia - Rozi, Ahmad Fahrur Rozi; Mulawarman Hannase (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2025)
This paper discusses the dynamics of political Islam in the Southeast Asian region, particularly in Indonesia and Malaysia. Both countries have similar historical records of political Islam, but they appear to have moved in different directions after the arrival of colonialism and into the modern contemporary era. A comparative method was used as a research analysis method to find the similarities and differences between political Islam in the two countries. Moreover, a historical approach is used as a tool to examine the historical record of the dynamism of political Islam in both countries. Through this method and approach, the author finds three similarities: Indonesia and Malaysia both adhere to a hadārithe substance of Islamic values rather than the formalisation of Islam, and strive to create a civilised Muslim society (Madani Society and Islam Haḍāri). Meanwhile, the differences are the use of the word ‘Islam’ as a symbol in the state constitution and the involvement of the government and non-government actors in the Islam ic political movement. In Malaysia, Islamic politics is dominated by the government elite, while in Indonesia, it tends to be dominated by Islamic mass organizations.